Translation of basic research in cognitive science to HIV-risk: a randomized controlled trial. - Stacy, Alan W.; Nydegger, Liesl A.; Shono, Yusuke (Journal of Behavioral Medicine, 2019)
Many people enrolled in drug diversion programs are not receiving evidence-based prevention for HIV or hepatitis. This study translated basic research from cognitive science to increase screening for infection and condom use in this population. A parallel three-condition randomized trial was conducted in a drug diversion sample (N = 358), comparing a memory practice condition with two active control conditions. Outcomes were condom use frequency and testing for infection (hepatitis B/C, HIV). At 3-month follow-up, participants in the memory practice condition were at least twice as likely (OR = 2.10 or greater, p <.01) to self-report testing compared to those in the control conditions and also reported more frequent condom use compared to a health education condition [B =.37, t(1) = 2.02, p =.02]. Basic research on memory can be effectively translated to brief interventions on infection screening and risk prevention in existing drug diversion programs.